SUBSTITUTION ON A DAY AGE OF RIPE BANANA TO QUALITY STEAMED SPONGE CAKE - Sari, Wenggi Sartika; Syarif, Wirnelis; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2015)
This study aimed to analyze the effect of substitution on a day age of ripe bananas as much as 15%, 20% and 25% of the wheat flour that used to quality volume (expands), shape (spherical and chapped 3 parts on the surface and form a neat), color (white), texture (soft texture and smooth texture porous pores), aroma (a day age of ripe bananas), aroma (vanilla), and taste (sweet and taste of a day age of ripe bananas). The research is a pure experiment with completely randomized design method using three repetitions by 5 panelists. The results showed that Fcount > Ftable so that the substitution of a day age of ripe bananas to the quality of steamed sponge effect on the quality of it shape (spherical and chapped 3 parts on the surface), color (white), texture (soft), and aromas (ripe bananas a day), but not effect on the quality of the volume (expands), shape (neat), texture (fine pores), aroma (vanilla), taste (sweet) and taste (a day age of ripe bananas) and highest value contained in the substitution of 15% (X1).Keywords: A Day Age of Ripe Bananas, Steamed Sponge, Quality, Substitution1Prodi